Caregiver-supported nursing intervention for smoothing the transition from pediatric intensive care units to ward: protocol for a pre-post interventional study - Panda, Shramana Ray; Shetty, Asha P.; Dwibedi, Bhagirathi (International Journal of Research in Medical Sciences, 2025)
Background: Transitioning patients from pediatric intensive care units (ICUs) to general wards involves high risk for adverse events, highlighting the need for structured, patient-centered transition protocols. Currently, informal transfer processes often compromise patient safety and care quality, underscoring the value of a formalized model to guide this critical phase. Methods: This pre-post interventional study will involve caregivers of pediatric patients preparing for ICU discharge. The intervention includes a structured transition model, with targeted training and support provided to caregivers to enhance their engagement and readiness. Data on caregiver satisfaction, understanding, and quality of care metrics will be collected pre- and post-intervention to evaluate outcomes. Conclusions: The structured intervention is anticipated to enhance caregivers' comprehension and satisfaction with the transition process, while promoting improved care quality and safety during the critical shift from ICU to ward Trial registration: The study protocol is registered in CTRI/2023/07/054787.